1998
DOI: 10.1007/s005850050721
|View full text |Cite
|
Sign up to set email alerts
|

Effects of geomagnetic activity on the mesospheric electric fields

Abstract: Abstract. The results of three series of rocket measurements of mesospheric electric ®elds carried out under dierent geomagnetic conditions at polar and high middle latitudes are analysed. The measurements show a clear dependence of the vertical electric ®elds on geomagnetic activity at polar and high middle latitudes. The vertical electric ®elds in the lower mesosphere increase with the increase of geomagnetic indexes u p and u p . The simultaneous increase of the vertical electric ®eld strength and ion condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Moreover, 15 the energetic charged particle precipitation may "short out" such existing mesospheric and stratospheric electric fields, producing either an increase or decrease of E z (Hale and Croskey, 1979;Zadorozhny et al, 1994). In particular, in Holzworth et al (1987), Zadorozhny et al (1994), Zadorozhny and Tyutin (1998) and Kasatkina and Shumilov (2005) it was shown that the increase of the vertical component of the electric field 20 strength during a GLE event is possible if the total aerosol change increases with the ion pair production rate increase more than that of the conductivity. For example, this phenomenon may be considered in the charged aerosol gravitational sedimentation physical mechanism (Aikin and Maynard, 1990;Zadorozhny et al, 1994;Zadorozhny and Tyutin, 1998…”
mentioning
confidence: 99%
“…Moreover, 15 the energetic charged particle precipitation may "short out" such existing mesospheric and stratospheric electric fields, producing either an increase or decrease of E z (Hale and Croskey, 1979;Zadorozhny et al, 1994). In particular, in Holzworth et al (1987), Zadorozhny et al (1994), Zadorozhny and Tyutin (1998) and Kasatkina and Shumilov (2005) it was shown that the increase of the vertical component of the electric field 20 strength during a GLE event is possible if the total aerosol change increases with the ion pair production rate increase more than that of the conductivity. For example, this phenomenon may be considered in the charged aerosol gravitational sedimentation physical mechanism (Aikin and Maynard, 1990;Zadorozhny et al, 1994;Zadorozhny and Tyutin, 1998…”
mentioning
confidence: 99%
“…Proceedings of Eleventh Workshop "Solar Influences on the Magnetosphere, Ionosphere and Atmosphere" Primorsko, Bulgaria, June 3÷7, 2019 Features of vertical electric fields in mesosphere and stratosphere In a series of rocket experiments above Heiss Island (80°37N, 58°03E) and above southern Indian Ocean [Zadorozhny et al, 1998] found unusually large (~1 V/m) vertical electric field Ez in the mesosphere which still remain unexplained. Fig.3 demonstrates profiles of Ez in three cases above Indian Ocean.…”
Section: B) Measurements In Stratosphere At Middle Latitudes During Smentioning
confidence: 99%
“…The inherent current sources [119,120] in the mesosphere may generate large DC electric fields in the 50-70 km region [121], which has been observed via rocket measurements [122,123] and remotely via a series of MF radar measurements [124][125][126][127]. The large DC electric fields increase the electron temperature and effective collision frequency in D-region.…”
Section: Phenomenamentioning
confidence: 99%